Nuclear Batteries and Radioisotopes - Prelas, Mark; Boraas, Matthew; De La Torre Aguilar, Fernando; Seelig, John-David; Tchakoua Tchouaso, Modeste; Wisniewski, Denis (Lecture Notes in Energy, 2016)
This book explains the physics of nuclear battery operation. It provides a comprehensive background that allows readers to understand all past and future developments in the field. The supply and cost of radioisotopes for use in applications (focused on nuclear batteries) are covered in the initial sections of the text. The interaction of ionizing radiation with matter is discussed as applied to nuclear batteries. The physics of interfacing the radioisotopes to the transducers which represent the energy conversion mechanism for nuclear batteries are described for possible nuclear battery configurations. Last but not least the efficiencies of nuclear battery configurations are discussed combined with a review of the literature on nuclear battery research.